Pola Penyebaran Infeksi Covid-19 di Provinsi Papua Tahun 2020 - Indra Taufik Sahli; Asrianto Asrianto; Risda Hartati; Novianti Yoyo Simega (GEMA KESEHATAN, 2020)
Covid-19 is a disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus. data as of July 27, Covid 19 sufferers in Papua reached 2130 cases. The research objective was to determine the pattern of the spread of Covid 19 infection in Papua Province in 2020. The descriptive research method was cross-sectional design, using secondary data obtained from the Covid 19 Task Force Team of the Papua Provincial Health Office. The results showed the increase in May as many as 533 cases. The highest number of people with Covid-19 based on age is 20-60 years old. Based on sex, the highest percentage is male, this is due to the natural immune response and the immune response acquired during viral infection between women and men. Based on the evidence that shows that Covid 19 infection attacks many non-Papuan tribes compared to Papuans. The incidence of Covid 19 cases of ethnicity related to socio-economic, cultural, genetic factors, vulnerability to susceptibility or response to infection. The number of cases recovered against Covid 19 for the period March 22 to July 22 2020 the number of cases was 1956, while the number of cases died was 23 people. The cure rate is the result of many factors, which indicate the patient's physiological ability to attack Coronavirus. Conclusion; The highest number of males in May was 533 people, the age range of sufferers was 20 - 60 years, more men than women, less ethnic Papuans than non-Papuan ethnics, 27 July the number of people who recovered in 1956 while 23 people died.